Nanoparticles as Vectors to Tackle Cancer - Chengchen Duan (MDPI AG, 2021)
The aim of this Special Issue, “Nanoparticles for cancer therapy”, was to offer readers a comprehensive and up-to-date insight into the various applications of nanoparticles in cancer treatments [...]